A Study of the Implementation of PSAK 74 on Firm's Value of Insurance Companies in Indonesia - Aulia Veronica Julyono; Vena Purnamasari (Journal of Management and Business Environment (JMBE), 2024)
Firm’s value plays an important role for both company management and investors in investment decisions. Often, net profit or revenue is closely related to the creation of firm’s value. This research examines whether the application of the Pernyataan Standar Akuntansi Keuangan (PSAK) or Indonesian Financial Accounting Standards Board 74 affects company value as measured using Tobin’s Q. Standards for insurance company contracts have changed based on the adoption of IFRS 17, and are still being prepared and conducted in-depth studies. This research uses a quantitative approach with panel data regression testing using STATA. Data was collected in the form of secondary data on insurance companies listed on the Indonesia Stock Exchange from 2012 to 2022, using a purposive sampling method. The results of the research show that operational profit (loss) from the new face of insurance company financial reports has a positive effect, while insurance company investment profit (loss) has a negative effect on company value. This research expands the study of the implications of implementing PSAK 74 for insurance companies in the future.